Responses of grassland soil mesofauna to induced climate change - Iwona Gruss; Marta Czarniecka-Wiera; Sebastian Świerszcz; Magdalena Szymura; Tomasz Szymura; Małgorzata W. Raduła (Scientific Reports)
Abstract Climate change can significantly affect the below and above-ground ecosystems. This study aimed to test the effects of induced climate change on the composition of soil mesofauna and vascular plant species in semi-natural grasslands. Open-top chambers (OTCs) were used to manipulate climatic conditions. The research was carried out over three years in two semi-natural grasslands in south-west Poland (Central Europe). Changes in soil mesofauna (Collembola and Acari) and vegetation characteristics under OTC treatment were evaluated and compared to untreated control sites. Treatment with OTC significantly increased the abundance of Oribatida mites (up to 42%) but decreased the abundance of Gamasida (by 21%), indicating contrasting responses of the Acari subgroups to warming. Collembola diversity was significantly reduced under OTC conditions, as reflected in the lower Margalef, Simpson, and Shannon–Wiener indices. Furthermore, the abundance of epigeic Collembola increased under OTC. Redundancy analysis (RDA) revealed that plant traits explained 37.91% of the variation in mesofauna structure. Structural Equation Modelling (SEM) further supported these findings, showing that climate exerted a strong negative effect on soil quality, which in turn had a pronounced positive influence on plant quality (total effect = 0.678). Plant quality significantly enhanced soil fauna abundance (total effect = 0.264), while the overall impact of climate on soil fauna was negative (– 0.231), primarily via indirect pathways. These findings suggest that climate change in grassland ecosystems can disrupt the ecological balance of soil fauna by modifying their responses to environmental variables. The SEM results emphasise the cascading nature of these effects, from climate to soil, vegetation, and ultimately soil fauna, highlighting the importance of indirect environmental pressures. Conserving plant diversity remains essential to buffer against climate-driven disruptions and maintain ecosystem stability.